Daily Spiritual Experiences in a Biracial, Community-based Population of Older Adults - Skarupski, Kimberly A. (2010)
OBJECTIVES: The objectives of this study were to describe the levels of daily spiritual experiences in community-dwelling older adults, to compare levels of spiritual experiences with levels of prayer and religious service attendance, and to examine demographic and psychosocial correlates of spiritual experiences. METHOD: The data came from 6,534 participants in the Chicago Health and Aging Project, an ongoing population-based, biracial (65% African American) study of risk factors for incident Alzheimer’s disease among older adults. A five-item version of the Daily Spiritual Experience Scale (DSES) was used in the study. Multivariable linear regression models were used to examine the relationship between sociodemographic and psychosocial factors and DSES scores. RESULTS: The majority of participants reported having spiritual experiences at least daily. In the bivariate analyses, African Americans and women had higher DSES scores than Whites and men, respectively (p’s < 0.001). Prayer and worship were moderately associated with DSES scores. In the multivariable analyses, African American race, older age, female gender, better self-rated health, and greater social networks were associated with higher DSES scores, while higher levels of education and depressive symptoms were associated with lower DSES scores. CONCLUSION: We observed high levels of spiritual experiences and found that the DSES is related to, but distinct from traditional measures of religiosity. We found associations between DSES, demographic, and psychosocial factors that are consistent with findings for other R/S measures. Future research should test whether daily spiritual experiences contribute to our understanding of the relationship between R/S and health in older adults.